High‐resolution metabolic mapping of the cerebellum using 2D zoom magnetic resonance spectroscopic imaging. Issue 5 (7th December 2020) - Emir, Uzay E.; Sood, Jaiyta; Chiew, Mark; Thomas, Micheal Albert; Lane, Sean P.
Abstract : Purpose: The human cerebellum plays an important role in the functional activity of the cerebrum, ranging from motor to cognitive systems given its relaying role between the spinal cord and cerebrum. The cerebellum poses many challenges to Magnetic Resonance Spectroscopic Imaging (MRSI) due to its caudal location, susceptibility to physiological artifacts, and partial volume artifacts resulting from its complex anatomical structure. Thus, in the present study, we propose a high‐resolution MRSI acquisition scheme for the cerebellum. Methods: A zoom or reduced field of view (rFOV) metabolite‐cycled MRSI acquisition at 3 Tesla, with a grid of 48 × 48, was developed to achieve a nominal resolution of 62.5 μL. Single‐slice rFOV MRSI data were acquired from the cerebellum of 5 healthy subjects with a nominal resolution of 2.5 × 2.5 × 10 mm 3 in 9.6 min. Spectra were quantified using the LCModel package. A spatially unbiased atlas template of the cerebellum was used to analyze metabolite distributions in the cerebellum. Results: The superior quality of the achieved spectra‐enabled generation of high‐resolution metabolic maps of total N‐acetylaspartate, total Creatine (tCr), total Choline (tCho), glutamate+glutamine, and myo‐inositol, with Cramér‐Rao lower bounds below 50%. A template‐based regions of interest (ROI) analysis resulted in spatially dependent metabolite distributions in 9 ROIs. The group‐averaged high‐resolution metabolite maps across subjects increased the contrast‐to‐noise ratio between cerebellum regions. Conclusion: These findings indicate that very high‐resolution metabolite probing of the cerebellum is feasible using rFOV or zoomed MRSI at 3 Tesla.